Interaction of the SXT/R391 element ICEPmiJpn1 with its natural host Proteus mirabilis - Douglas Lyra de Holanda Fonseca; Gaby Soares Scheunemann; Bruna Nakanishi Fortes; Kelly Ishida; Rodrigo S. Galhardo (Microbiology Spectrum)
ABSTRACT Integrative and conjugative elements (ICEs) of the SXT/R391 family are mobile genetic elements that integrate into the bacterial host chromosome and can be transferred horizontally, spreading antimicrobial resistance genes. Our study aimed to evaluate aspects of the relationship between ICEPmiJpn1, one of the most widespread SXT/R391 variants, with its natural host Proteus mirabilis. For this investigation, we used isogenic strains (containing or not the ICEPmiJpn1) that enabled us to evaluate the influence of this element on several physiological aspects of P. mirabilis as well as the effect of different P. mirabilis genetic backgrounds on the conjugative transmission of the element. ICEPmiJpn1 did not impact the fitness, self-recognition, swarming, pathogenicity, and persistence abilities of this bacterium but increased biofilm formation in one strain. Additionally, conjugative transfer of the element to Escherichia coli is widely variable when different P. mirabilis strains are used as donors in mating assays. Our results indicate that ICEPmiJpn1 has no adverse effects on the physiology or pathogenicity of P. mirabilis, reflecting a stable association between this element and its host. Furthermore, the findings support the notion that ICE transfer between bacteria is influenced not only by element-specific regulators but also by strain-specific factors.IMPORTANCEMobile genetic elements play a key role in the spread of antimicrobial resistance, raising concerns about multidrug-resistant bacteria, yet their interactions with bacterial hosts are not well characterized. This study explores the relationship between ICEPmiJpn1, a globally distributed SXT/R391 integrative and conjugative element (ICE), and its natural host Proteus mirabilis, revealing minimal effects on bacterial fitness and pathogenicity. Nevertheless, strain-specific factors significantly influence conjugative transfer. These findings highlight the need for further research on host-dependent regulatory mechanisms that drive the spread of these elements. Understanding these dynamics is essential for developing strategies to mitigate the dissemination of antibiotic resistance in clinically relevant bacterial populations.